Electron-enhanced reactions responsible for photoluminescence spectrum change in II-VI compounds - Korsunskaya, N. E.; Markevich, I. V.; Dzhumaev, B. R.; Borkovskaya, L. V.; Sheinkman, M. K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Electron-enhanced reactions in II-VI compounds are shown to be caused by the presence of some mobile defects which diffusion is not enhanced under excitation. At the same time, electron-enhanced diffusion can be imitated in these reactions due to carrier trapping by deep centers that do or even do not take part in the reaction. To elucidate the real defect reaction mechanism a detailed study is required in every case. For this purpose, a method of mobile defect detection and their diffusion characteristic direct investigation has been elaborated.